Major weather regime changes over Southeast Asia in a near-term future scenario - Cindy Bruyère (2018)
© Inter-Research 2017. A near-term future climate scenario over Southeast Asia is generated using a dynamical downscaling approach, and a process-level understanding of the regional climate change is developed by breaking down regional climate into the major rainfall agents of monsoon flow and tropical cyclone activity. The Weather Research and Forecasting model, driven by a Community Climate System Model simulation under the A2 forcing scenario, is used to simulate current and near-term future climate in the Southeast Asia region. Under current climate conditions the model is able to capture the major climate characteristics of the region including the seasonal cycle in tropical cyclone frequency and monsoon precipitation. A near-term future simulation produces an overall increase in the intensity of precipitation events. The strengthening of the Meiyu front combined with an increase in tropical cyclone frequency contributes to this overall increase in precipitation. Future changes in monsoon timing are greater than historical decadal variability, with future onset delayed and future dissipation arriving earlier, reducing monsoon duration. In addition, a higher proportion of zonally-oriented tropical cyclone tracks and higher landfall risk are predicted. This near-term future scenario would result in heightened impacts on already vulnerable communities.